Nano-XRF of lung fibrotic tissue reveals unexplored Ca, Zn, S and Fe metabolism: a novel approach to chronic lung diseases - Bryan Falcones; Maik Kahnt; Ulf Johansson; Barbora Svobodová; Karin A. von Wachenfelt; Charlott Brunmark; Göran Dellgren; Linda Elowsson; Karina Thånell; Gunilla Westergren-Thorsson (Cell Communication and Signaling)
Abstract Synchrotron-radiation nano-X-Ray Fluorescence (XRF) is a cutting-edge technique offering high-resolution insights into the elemental composition of biological tissues, shedding light on metabolic processes and element localization within cellular structures. In the context of Idiopathic Pulmonary Fibrosis (IPF), a debilitating lung condition associated with respiratory complications and reduced life expectancy, nano-XRF presents a promising avenue for understanding the disease’s intricate pathology. Our developed workflow enables the assessment of elemental composition in both human and rodent fibrotic tissues, providing insights on the interplay between cellular compartments in chronic lung diseases. Our findings demonstrate trace element accumulations associated with anthracosis, a feature observed in IPF. Notably, Zn and Ca clusters approximately 750 nm in size were identified exclusively in IPF samples. While their specific role remains unclear, their presence may be associated with disease-specific processes. Additionally, we observed Fe and S signal colocalization in 650-nm structures within some IPF cells. Fe-S complexes in mitochondria are known to be associated with increased ROS production, suggesting a potential connection to the disease pathology. In contrast, a bleomycin-induced fibrosis rodent model exhibits a different elemental phenotype with low Fe and increased S, Zn, and Ca. Overall, our workflow highlights the effectiveness of synchrotron-based nano-XRF mapping in analyzing the spatial distribution of trace elements within diseased tissue, offering valuable insights into the elemental aspects of IPF and related chronic lung diseases.